Synthesis and Evaluation of Fluorine-18-Labeled L-Rhamnose Derivatives - Xiang Zhang; Falguni Basuli; Zhen-Dan Shi; Swati Shah; Jianfeng Shi; Amelia Mitchell; Jianhao Lai; Zeping Wang; Dima A. Hammoud; Rolf E. Swenson (Molecules, 2023)
The use of radiolabeled glucose for PET imaging resulted in the most commonly used tracer in the clinic, 2-deoxy-2-[18F]fluoroglucose (FDG). More recently, other radiolabeled sugars have been reported for various applications, including imaging tumors and infections. Therefore, in this study, we developed a series of fluorine-18-labeled L-rhamnose derivatives as potential PET tracers of various fungal and bacterial strains. Acetyl-protected triflate precursors of rhamnose were prepared and radiolabeled with fluorine-18 followed by hydrolysis to produce L-deoxy [18F]fluororhamnose. The overall radiochemical yield was 7–27% in a 90 min synthesis time with a radiochemical purity of 95%. In vivo biodistribution of the ligands using PET imaging showed that 2-deoxy-2-[18F]fluoro-L-rhamnose is stable for at least up to 60 min in mice and eliminated via renal clearance. The tracer also exhibited minimal tissue or skeletal uptake in healthy mice resulting in a low background signal.